The surface electronic structure of silicon terminated (100) diamond. (23rd May 2016) - Schenk, A K; Tadich, A; Sear, M J; Qi, D; Wee, A T S; Stacey, A; Pakes, C I
Abstract: A combination of synchrotron-based x-ray spectroscopy and contact potential difference measurements have been used to examine the electronic structure of the (3 × 1) silicon terminated (100) diamond surface under ultra high vacuum conditions. An occupied surface state which sits 1.75 eV below the valence band maximum has been identified, and indications of mid-gap unoccupied surface states have been found. Additionally, the pristine silicon terminated surface is shown to possess a negative electron affinity of −0.86 ± 0.1 eV.